Robotics: Science and Systems II 2006
DOI: 10.15607/rss.2006.ii.005
|View full text |Cite
|
Sign up to set email alerts
|

Self-supervised Monocular Road Detection in Desert Terrain

Abstract: Abstract-We present a method for identifying drivable surfaces in difficult unpaved and offroad terrain conditions as encountered in the DARPA Grand Challenge robot race. Instead of relying on a static, pre-computed road appearance model, this method adjusts its model to changing environments. It achieves robustness by combining sensor information from a laser range finder, a pose estimation system and a color camera. Using the first two modalities, the system first identifies a nearby patch of drivable surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
241
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(254 citation statements)
references
References 13 publications
(12 reference statements)
0
241
0
2
Order By: Relevance
“…Dahlkamp et al (2006) apply a Kalman filter to estimate the robot pose based on measurements from two differential GPS systems and a six-degree-of-freedom inertial measurement unit (IMU). Based on the pose estimation, 2D LIDAR points are projected into a 3D frame.…”
Section: Lidar/vision-basedmentioning
confidence: 99%
“…Dahlkamp et al (2006) apply a Kalman filter to estimate the robot pose based on measurements from two differential GPS systems and a six-degree-of-freedom inertial measurement unit (IMU). Based on the pose estimation, 2D LIDAR points are projected into a 3D frame.…”
Section: Lidar/vision-basedmentioning
confidence: 99%
“…Since our system uses road paint as its primary information source, in the absence of road paint it is no surprise that no lane estimate ensues. Other environmental cues such as color and texture may be useful in such situations (Dahlkamp et al 2006). …”
Section: System Confidencementioning
confidence: 99%
“…Other work has previously been done in road detection where we mention the work by Fernandez and Price [18] who used region growing in HSI color values to find the road borders. Others include Dahlkamp et al [19], who used self-supervised learning on color images to extend roads found by LADAR. In the area of stereo-vision Soquet et al [20] used a stereo-based color segmentation algorithm to determine road segments.…”
Section: Path Findingmentioning
confidence: 99%
“…These can be computed recursively (18)(19) and are constrained to be nonnegative. The new width profile, w R i , of row i is computed as and takes into account spatial coherency in each row.…”
Section: B Computing the Path Profilementioning
confidence: 99%